Information technology. International standardized profile RB. Relaying the connection-mode network service. Definition of profile RB51.1111, relaying the connection-mode network service betweeen CSMA/CD LAN subnetworks and PSDNs using virtual calls over a PSTN leased line permanent access Part 4, (15th November 1998) - British Standards Institution,
No abstract available